A systematic review and meta-analysis of magnetic resonance imaging measurement of structural volumes in posttraumatic stress disorder. Issue 1 (30th April 2015) - O'Doherty, Daniel C.M.; Chitty, Kate M.; Saddiqui, Sonia; Bennett, Maxwell R.; Lagopoulos, Jim
Abstract: Posttraumatic stress disorder (PTSD) is a debilitating condition associated with mild to moderate cognitive impairment and with a prevalence rate of up to 22% in veterans. This systematic review and quantitative meta-analysis explore volumetric differences of three key structural brain regions (hippocampus, amygdala and anterior cingulate cortex (ACC)), all of which have been implicated in dysfunction of both salience network (SN) and default mode network (DMN) in PTSD sufferers. A literature search was conducted in Embase, Medline, PubMed and PsycINFO in May 2013. Fifty-nine volumetric analyses from 44 articles were examined and included (36 hippocampus, 14 amygdala and nine ACC) with n =846 PTSD participants, n =520 healthy controls (HCs) and n =624 traumatised controls (TCs). Nine statistical tests were performed for each of the three regions of interest (ROIs), measuring volume differences in PTSD subjects, healthy and traumatised controls. Hippocampal volume was reduced in subjects with PTSD, with a greater reduction in the left hippocampus. A medium effect size reduction was found in bilateral amygdala volume when compared with findings in healthy controls; however, no significant differences in amygdala volume between PTSD subjects and trauma-exposed controls were found. Significant volume reductions were found bilaterally in the ACC. While often well matched with their respective control groups, the samples of PTSD subjects composed from the source studies used in the meta-analyses are limited in their homogeneity. The current findings of reduced hippocampal volume in subjects with PTSD are consistent with the existing literature. Amygdala volumes did not show significant reductions in PTSD subjects when compared with volumes in trauma-exposed controls—congruous with reported symptoms of hypervigilance and increased propensity in acquisition of conditioned fear memories—but a significant reduction was found in the combined left and right hemisphere volume analysis when compared with healthy controls. Bilateral volume reductions in the ACC may underpin the attentional deficits and inabilities to modulate emotions that are characteristically associated with PTSD patients. Highlights: Up to date meta-analysis that includes 44 papers. Covers the three main brain regions implicated in PTSD. PTSD is associated with reduced hippocampal volumes. PTSD is associated with reduced anterior cingulate volumes. PTSD is not associated with reduced amygdala volumes.